This preview shows page 1. Sign up to view the full content.
Unformatted text preview: x – 5, find and simplify for f(a+3).
Substitute a+3 for every x and simplify:
f(a+3) = 2(a+3)2 + 3(a+3) – 5 =2(a2+6a+9)+3(a+3)5 =2a2+12a+18+3a+95 =2a2+15a+22 Function Notation Factoring polynomial expressions is not quite the same as factoring numbers, but the concept is very similar. When factoring numbers or factoring polynomials, you are finding numbers or polynomials that divide out evenly from the original numbers or polynomials. But in the case of polynomials, you are dividing numbers and variables out of expressions, not just dividing numbers out of numbers. 5.3Factoring Previously, you have simplified expressions by distributing through parentheses, such as:
2(x + 3) = 2(x) + 2(3) = 2x + 6 Simple factoring in the context of polynomial expressions is backwards from distributing. That is, instead of multiplying something through a parentheses, you will be seeing what you can take back out and put in front of a parentheses, such as:
2x + 6 = 2(x) + 2(3) = 2(x + 3) The trick is to see what can...
View Full Document